Cycle of lectures within the seminar Anthropological Agora in 2018 - Ljubica Milosavljević (University of Belgrade, 2018)
This year's cycle of lectures within the seminar Anthropological agora, which is being organized continuously and successfully by the Institute of Ethnology and Anthropology, Faculty of Philosophy, University of Belgrade, was characterized by thematically extremely interesting presentations.